Hotspot Analysis of Prefabricated Buildings from Different Perspectives by Literature Analyzing - Fan , Junchi (Highlights in Science, Engineering and Technology, 2024)
Prefabricated building is a new type of building construction technology, but it is still a developing industry that needs constant exploration and improvement. Based on academic papers related to prefabricated buildings in CNKI and WOS literature databases, this paper uses CiteSpace software as an analysis tool to analyze the research hotspots of prefabricated buildings in recent years, and summarizes its future research direction. The results of this paper show that the amount of literature on prefabricated buildings is increasing year by year worldwide. At present, the main research countries of prefabricated buildings are China, Australia and the United States. In recent years, the structural design and standardization of prefabricated buildings will continue to be the focus of attention. With the solution of related problems, prefabricated construction will become an effective and low-cost construction method. The analysis in this paper provides new insights into the development trend and future prospects of this emerging industry. Despite the convenience and sustainability benefits of prefabricated building technology, it still needs to be further refined. These findings contribute to a better understanding of the dynamics shaping the prefabricated construction industry and provide guidance for future research and development efforts.